Inconsistent Condom Use Among Male University Students in Northern Thailand - Jakkrite Pinyaphong (2018)
© 2018, © 2018 APJPH. University students are at increased risk of HIV infection, but little is known about the determinants of inconsistent condom use among them. The study aims to assess the association of sociodemographic, individual, dyadic, and social factors with inconsistent condom use among male university students. Of 1091 participants, 67.0% had sexual intercourse, though 64.4% had inconsistent condom use. It was found that “did not use a condom at first sexual intercourse” (adjusted odds ratio [AOR] 6.1; CI, 3.7-10.1), “history of STIs” (AOR, 2.1; CI, 1.0-4.2), low “self-efficacy” (AOR, 2.4; CI, 1.3-4.7), “perception that condom use reduces pleasure” (AOR, 1.4; CI, 1.0-2.1), and “high subjective norm” (AOR, 1.9; CI, 1.3-2.8) were associated with increased odds of inconsistent condom use. Condom use should be promoted from the onset of sexual activity to establish a habit of safe sex practices and for improvement in self-efficacy of condom use. Emphasis must be laid on pleasure-enhancing benefits of condom use and changing social norms.